RESOLUSI PENANGANAN GAFATAR PASCA DIBUBARKAN OLEH PEMERINTAH PROVINSI BANGKA BELITUNG - Hadarah Rajab (IAIN Surakarta, 2016)
This study attempts to describe activity GAFATAR in Bangkabelitung after dissolved.The results of research suggest that after the dissolution of GAFATAR, his followers still keep his view that the organization GAFATAR did not teach something subverted from tenets or the rule of law or customary is in this country, and not fund that members of GAFATAR know are the anew after Muhammad saw. They feel this would be a belief where confidence any will be guaranteed in national unity of the republic of Indonesia. On the other hand, after the dissolution of GAFATAR phenomenon, on the surface is looks calmly but still needs to be alert by Karen due to the emergence of GAFATAR the life of his followers be chaotic and misery of then responsibility the leaders GAFATAR there is no.Joy and this phenomenon people who were subjected to experienced depress social in the massif.